Perkembangan Psikologi Anak pada Kasus Bullying di SDN Cikampek Pusaka I - Gunawan, Iwan; Wahyudin, Undang Ruslan (MASALIQ, 2023)
Bullying can occur verbally, physically or psychologically. This action has a negative effect on the mental health of adolescents, one of which is anxiety. Indonesia is one of the countries with the highest cases of bullying. The report of bullying that happened to students of one of the SDN Cikampek Pusaka I in 2022, is one example of the high incidence of this action in adolescents. This study aims to determine the impact of bullying with anxiety. The subjects in this study were students of class I -VISDN Cikampek Pusaka I Karawang Regency. The method used in this study is Qualitative with a class action approach with a total sample of 30 respondents using purposive sampling techniques. This study used the Depression Anxiety Stress Scale (DASS) to measure the anxiety scale. The results of the spearman's rho statistical test obtained a correlation value (r) of 0.51 with a significant level (ρ) of 0.00 indicating that the value of ρ < α (α = 0.05). The conclusions of this study show that there is an impact of bullying with anxiety